System strengthening approaches for scaling up development outcomes from agricultural research. Knowledge sharing workshop. 13‐15 November 2018, Addis Ababa, Ethiopia - Vugt, D. van; Lemaga, B.; Heck, S.; Brouwers, J. (International Potato Center, 2019)
CIP organized a workshop to share, review and analyze experiences and results from system strengthening approaches across the potato and sweetpotato programs in Ethiopia, Malawi and Mozambique, as well as other initiatives that are working towards the same goal. The workshop brought together some fifty participants from Ethiopia, Malawi and Mozambique, together with CIP staff from its headquarters in Lima and the CIP Africa Regional Office, as well as a delegation from Irish Aid and other interested partners from West Africa.